Hypertrophic Pulmonary Osteoarthropathy in Acquired Immunodeficiency Syndrome. Case Report and Review - Carreiro-Rodríguez, Manuel; Hernández-Blanca, Dorylu; Manuel Fernández, Luis; Montes de Oca, Ivette; Castillo, Eglee; Sánchez, José Luis (Investigación Clínica, 2009)
We describe a case of hypertrophic pulmonary osteoarthropathy (HPOA) in an adult patient with acquired immunodeficiency syndrome (AIDS). This is the ninth case of HPOA associated with AIDS in adults, reported in the literature. The presence of pulmonary tuberculosis was also suspected, based on clinical grounds. Cases of clubbing associated with AIDS infection are reviewed